Gold Coast (2015) and Danish economies of colonial guilt. Issue 2 (2nd April 2018) - Körber, Lill-Ann
ABSTRACT: The article discusses Daniel Dencik's feature film Gold Coast (2015), about the last phase of Danish colonialism in today's Ghana, as an example for recent representations of Danish colonial history. Combining historian of ideas Astrid Nonbo Andersen's exploration of Danish narratives of "innocent colonialism", Gloria Wekker's concept of "White Innocence", and film historian Thomas Elsaesser's model of "guilt economies" as a feature of the legacy of perpetrator nations (2014), the article provides a framework within which to examine figurations of colonial guilt and innocence in Gold Coast . The main argument is that the film's treatment of colonial guilt primarily takes the form of maintenance of innocence. It thereby contradicts the challenges currently being pitted elsewhere against the narrative of innocent colonialism.